Pendulum type dynamic absorbeapplications - Diveyev, B.; Hrycaj, V.; Koval, T.; Teslyuk, V. (Національний університет "Львівська політехніка", 2009)
Розглянуто методи декомпозиції і синтезу числових схем на базі дискретно-неперервних модальних методів та виконано аналіз шляхів дослідження поведінки складних механізмів, зважаючи на їхню взаємодію з системою поглиначів динамічної вібрації. The main aim of this paper is pendulum type dynamic vibration absorbe attached to the elongated element design with taking into account complex machines dynamic Methods of decomposition and the numerical schemes syntethesis are consideed on the basis discrete-continuum modal method. Investigtion of complicated machines in view of their interaction with system of dynamic vibration absorbers is under iscussion.
Keywords: Вібрація; поглинач; маятник; vibration; absorber; pendulum